Benthonic Foraminifera from Lahave Estuary - Allen, Ralph; Roda, Robert (Atlantic Geology, 1977)
The five most numerous species of benthonic foraminifera sampled from the LaHave River estuary in Nova Sootia were used to define two major faunal assemblage zones. These are the upper estuarine and transitional zones of a "transitional" type of estuary as defined by Scott et al (1977). The transitional zone is subdivided into upper and lower subzones. Foraminiferal distribution in the study area appears to be determined by sediment patterns ao water temperatures and salinity show little variation.